ANALISIS MODEL “AISDALSLOVE” TERHADAP PERSEPSI KONSUMEN MOBILE ADVERTISING TELKOMSEL - Yanti, Afsari (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2016)
The amount of fraud committed using SMS makes the consumer becomes afraid and doubt when they got promotional message delivered via SMS.   Telkomsel as the biggest provider in Indonesia have benefit to provide advertising which can reach potential customer in all areas of Indonesia.  Telkomsel has the advantage to be able to cooperate with advertisers or manufacturers to provide information or promotions that can reach their customers.. Mobile Advertising Service become one of the leading products for telco industries.   SMS advertising deployment was done using two methods, namely using targeted SMS and SMS Location-Based Advertising LBA). Through  several  stages  using AISDALSLove   model  theory,  the  practice  of marketing  communications  via SMS can be seen from the aspect  of Attention, Interest,  Search, Desire,  Action, Like or Dislike,  Share and Love. The findings of this qualitative study found that the perception of consumers about the services of Mobile Advertising SMS Blast from PT. Telkomsel. The results of this research provides an overview of the perception from individual consumers who receive SMS.   Message or promotions as what it can attract the attention of consumers. The use of Sender ID are important in maintaining the credibility of a product in conveying a message or promotion..